2014
DOI: 10.1177/8755123314553130
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Teach Graduate Students

Abstract: This study examined our perceptions as a music education professor and three PhD students as we conducted a self-study of our individual and collective experiences teaching graduate students. We framed our work around the key question: How do PhD students describe experiences specifically in relation to perceived potential as teachers of graduate students in higher education? Findings concerning graduate teaching included (a) views of graduate teaching changed with increased experience, and (b) confidence incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Given concerns expressed by the participants and authors of the music education literature described, we were interested in examining IP with respect to the primary responsibilities of music education faculty positions (Bond & Koops, 2014; Conway et al, 2016; Martin, 2016; Pellegrino et al, 2014). We were interested in whether IP could explain some of the feelings of anxiety about teaching and research that participants in those studies expressed or provide an explanation for why some music education faculty do not continue to undertake and publish research after completing the doctorate (Sims, 2016; Sims & Cassidy, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Given concerns expressed by the participants and authors of the music education literature described, we were interested in examining IP with respect to the primary responsibilities of music education faculty positions (Bond & Koops, 2014; Conway et al, 2016; Martin, 2016; Pellegrino et al, 2014). We were interested in whether IP could explain some of the feelings of anxiety about teaching and research that participants in those studies expressed or provide an explanation for why some music education faculty do not continue to undertake and publish research after completing the doctorate (Sims, 2016; Sims & Cassidy, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Authors have raised questions and concerns about doctoral students’ preparation for various aspects of jobs as a music education professor (Conway, Palmer, Edgar, & Hansen, 2016; Kelly & VanWeelden, 2016). Responses to a survey of faculty who prepared doctoral music education students (Kelly & VanWeelden, 2016) indicated that it was important for doctoral students to observe and assist in undergraduate music education methods classes and student teaching, as well as to conduct their own research, present a poster, and present research at a conference, and that doctoral students had these experiences in almost all of the degree programs represented in the study.…”
mentioning
confidence: 99%
See 3 more Smart Citations